Knowledge and Views of Patients With Cardiovascular Disease Toward Pharmacogenomics in The United Arab Emirates - Maram O. Abbas; Azhar T. Rahma; Iffat Elbarazi; Bassam R. Ali; George P. Patrinos; Farah Nagy; Alya Osman; Reem K. Alneyadi; Anwar S. Alshamsi; Mohamed Alraqabani; Zeina Al‐Mahayri; Fatma Al‐Maskari (Clinical and Translational Science)
ABSTRACT Pharmacogenomics (PGx) can potentially tailor medication prescriptions to the genetic profiles of individuals, enhancing treatment outcomes and minimizing adverse drug reactions. This study assessed cardiovascular disease (CVD) patients' knowledge and views toward PGx testing in the United Arab Emirates (UAE). A cross‐sectional study was conducted among CVD patients attending multiple clinics using a validated, culturally adapted, and piloted bilingual questionnaire. Participants were invited via phone calls or in‐person contact at clinics. Data analysis was conducted using SPSS V.29, incorporating descriptive statistics and multivariable logistic regression. A total of 425 responses were analyzed; 67.5% were over 50 years old, and 67.5% held a bachelor's degree. Chronic diseases, excluding CVD, affected 65.2%, with 58.1% reporting medication side effects and 36.5% was hospitalized due to these effects. Knowledge varied, with 55.3% demonstrating good knowledge; 75.3% recognized DNA as gene‐based, while 47.5% understood PGx for predicting medication responses. Participants were grouped into three PGx perception clusters: Cluster 1 (33.17%) concerned about risks but valued PGx, Cluster 2 (40.23%) worried about privacy/costs, and Cluster 3 (26.58%) confident in PGx benefits. Safety was the top priority for 60.2% of respondents, 34.8% would not pay for PGx tets, and 35.3% preferred preemptive testing. Regression linked higher PGx knowledge to females, non‐healthcare workers, those with genetic diseases, and those hospitalized for side effects (p < 0.05). The study highlights a need for educational initiatives in the UAE to improve PGx literacy among CVD patients. The findings suggest that targeted awareness campaigns, policy interventions addressing privacy, and financial support could promote PGx wider adoption.